2015
DOI: 10.3233/jbr-150092
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of invasive pest Drosophila suzukii on berry production in the Province of Trento, Italy

Abstract: Abstract. BACKGROUND:The fly Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) is an endemic pest, native to Southern Asia which has recently invaded western countries. Since its detection in 2008 in California and Spain, it is now established in North America and in many European countries. OBJECTIVE: This paper aims to evaluate the pest's economic impact on the soft fruit industry in the Province of Trento, a region in the North East of Italy, which is one of the most productive soft fruit areas in Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 16 publications
1
68
0
1
Order By: Relevance
“…Trentino is one of the main production areas for soft fruits in Italy, accounting for an estimated 51% of Italian blueberry production in 2011, and for 40% of Italian raspberry production . Its produce is sold mainly on the domestic market . We assume that the demand for Trentino soft fruits is perfectly elastic, which means that a change in the price of the commodity has a noticeably negative effect on the quantity demanded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trentino is one of the main production areas for soft fruits in Italy, accounting for an estimated 51% of Italian blueberry production in 2011, and for 40% of Italian raspberry production . Its produce is sold mainly on the domestic market . We assume that the demand for Trentino soft fruits is perfectly elastic, which means that a change in the price of the commodity has a noticeably negative effect on the quantity demanded.…”
Section: Methodsmentioning
confidence: 99%
“…From these, and probably because of the low damage to production that was estimated for the period 2000–2012, the derived economic impact was seen to be reduced under a pest management strategy based on the use of insecticides, as the benefits of the intervention outweighed its cost . In fact, the economic impact of the pest in Trentino declined from an estimated 13% of potential revenue in the absence of management to 7% under an IPM strategy based on mass trapping, field sanitation and insecticide use . Moreover, in the USA, it was found that additional indirect effects on yield losses were produced, on the one hand, by the increase in commodity prices, which led to reduced revenue losses, and on the other hand, by potential labour shortages following reductions in wages, which made it more difficult for farmers to find workers for their fields …”
Section: Introductionmentioning
confidence: 99%
“…; De Ros et al. ). The species was first detected in the Upper Midwest in Wisconsin and Michigan in 2010, where it is now a major pest of blueberries ( Vaccinium spp.)…”
Section: Introductionmentioning
confidence: 97%
“…However, the analysis was limited to aggregated levels and neglected the costs of pest control. In a follow-up study, updated information was provided on infestation and damage recorded for the same region and crops over the period 2011–2013, and D. suzukii control costs were included [10]. Costs for materials, labour and infrastructure to implement surveillance, sanitation and pest control measures added up to total potential damage costs of one million EUR per year [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study, updated information was provided on infestation and damage recorded for the same region and crops over the period 2011–2013, and D. suzukii control costs were included [10]. Costs for materials, labour and infrastructure to implement surveillance, sanitation and pest control measures added up to total potential damage costs of one million EUR per year [10]. Ioriatti et al [11] estimated that in 2010 berry growers incurred a 25%–35% reduction of production value, depending on crops (more for blueberries and raspberries).…”
Section: Introductionmentioning
confidence: 99%